Polyamic acid imidazolium salt containing polyethylene glycol diamine and dianhydride monomer copolymer, preparation method and application
By using polyamic acid imidazole salt containing polyethylene glycol diamine and dianhydride monomer copolymer, a polyimide film with high thermal stability and excellent mechanical properties was prepared, and the silicon-based electrode in lithium-ion batteries was solved. The performance degradation caused by volume changes achieves the long-term stability of the battery under high temperature conditions and high circulation capacity.
Patent Information
- Application Number
- CN202411705037.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-14
AI Technical Summary
The volume of silicon-based electrodes in lithium-ion batteries changes greatly during the lithiation process, resulting in material breakage, loss of electrical contact and degradation of cycling performance, and the thermal stability and mechanical properties of existing polymer adhesives under high temperature conditions are insufficient.
Polyamic acid imidazole salt containing polyethylene glycol diamine and dianhydride monomer copolymer is prepared through specific polymerization conditions and processes to prepare polyamic acid with high thermal stability, excellent adhesive properties and good mechanical properties. Imine film.
It improves the thermal stability and mechanical properties of the silicon anode of lithium-ion batteries, extends the service life of the battery, and maintains excellent circulation capacity and stability under high temperature conditions.
Smart Images

Figure CN119431781A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a polyamic acid imidazole salt containing a copolymer of polyethylene glycol-type diamine and dianhydride-type monomers, a preparation method and application thereof, and belongs to the field of lithium ion batteries. Background Art
[0002] Lithium-ion batteries (LIBs) dominate the energy storage market due to their high energy density, high operating voltage, high reliability and high reliability. However, due to the low theoretical capacity of active materials, the current energy density level of lithium-ion batteries cannot meet the needs of large-scale applications. Therefore, to achieve high energy density in lithium-ion batteries, advanced materials with larger specific capacity must be used.
[0003] Silicon has an extremely high theoretical energy density (4200 mAh g -1 )、low reduction potential (0.2 V vs.Li / Li + ), and is inexpensive [Energy Environ. Sci. 2015, 8, 1224–1230.]. Therefore, the use of silicon in lithium-ion batteries appears to be an attractive approach to increase battery energy density and produce high-performance batteries. Silicon active materials undergo an alloying / alloying process ( , its theoretical capacity can reach about 10 times that of graphite [J.Electrochem. Soc. 1981, 128, 725–729.]. However, silicon-based electrodes undergo a volume change of up to 300% during lithiation (alloying), which may cause the silicon active material to break and fall off the copper current collector, resulting in loss of electrical contact, increased internal resistance and loss of active materials, seriously reducing the cycle performance [Chem. Soc. Rev. 2018, 47, 2145–2164.].
[0004] The use of highly functional polymer binder materials is considered to be the most effective way to improve the electrochemical performance of silicon anodes, considering efficient mass production and cost competitiveness. Therefore, polymer binders with excellent mechanical strength that can withstand large volume changes through interfacial interactions such as hydrogen bonding have been developed. For example, Lee et al. prepared a binder blended with polyaniline and polyacrylic acid (PAA) that exhibited remarkable electrochemical performance [RSCAdv. 2016, 6, 101622–101625.]. Zhao et al. developed poly(1-styrene-methyl methacrylate-methacrylic acid) as a conductive binder, which has high conductivity and adhesion due to the presence of methacrylic acid and styrene in the copolymer structure [Nano Lett. 2015, 15, 7927–7932.]. As a result, stable first cycle efficiency and long-term cycling performance were obtained. Ling et al. used a naturally abundant gum arabic polymer as a dual-functional binder; the hydroxyl groups of the polysaccharide have a strong binding affinity with silicon. Long glycoprotein chains improve the mechanical resistance to volume expansion of silicon electrodes [NanoEnergy 2015, 12, 178–185.]. However, the thermal stability, mechanical properties and adhesion properties of silicon electrodes still need to be further improved to provide a sufficiently long service life under high temperature conditions.
[0005] In view of this background, the present invention considers that polyimides (PIs) can be used as polymer binders with good mechanical properties, chemical resistance, thermal stability and moisture resistance. However, the polymerization of poly (amino acid) (PAmA) requires the use of highly polar organic solvents such as dimethylacetamide, dimethylformamide and N-methyl-2-pyrrolidone. Due to the environmental hazards and high prices of these organic solvents, their use in industry has been strictly restricted in recent years [Polym. Degrad. Stab. 2011,96, 2174–2180.].
[0006] In order to overcome this shortcoming, the present invention introduces a novel water-soluble polyimide precursor solution, which has the excellent thermal stability and mechanical strength of polyimide and can effectively inhibit electrode expansion; and introduces amino-terminated polyethylene glycol, which has flexible long-chain aliphatic hydrocarbons and oxygen-containing functional groups. The flexible aliphatic hydrocarbon main chain ensures the high elasticity of the polymer, and the oxygen-containing functional groups can coordinate with lithium ions to ensure good lithium ion conductivity. Summary of the invention
[0007] The purpose of the present invention is to provide a polyamic acid imidazole salt containing a copolymer of polyethylene glycol diamine and dianhydride monomers, a preparation method and an application thereof. The polyamic acid imidazole salt containing a copolymer of polyethylene glycol diamine and dianhydride monomers has high thermal stability, excellent adhesive properties and good mechanical properties.
[0008] The present invention provides a copolymer containing polyethylene glycol-type diamine and dianhydride monomers, wherein the main chain is composed of high molecular weight flexible ether bonds, flexible alkane chains and rigid aromatic skeletons, and is combined with piperidinium cations with high alkali stability. The copolymer is copolymerized with p-phenylenediamine, a highly reactive monomer, to obtain a high molecular weight polymer while retaining the high flexibility of polyethylene glycol. The obtained copolymer containing polyethylene glycol-type diamine and dianhydride monomers also demonstrates excellent chemical stability, film-forming properties, electrical conductivity and mechanical strength.
[0009] To achieve the above object, the technical solution adopted by the present invention is:
[0010] A polyamic acid imidazole salt containing a copolymer of polyethylene glycol-based diamine and dianhydride-based monomers, which is generated by reacting raw materials including a dianhydride component and a diamine component, and comprises the following repeating structural units:
[0011] ;
[0012] Wherein, x+y=1, 0≤x≤1, 0≤y≤1; For example, x is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or 1. For example, y is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or 1.
[0013] A represents at least one of the following groups: a tetravalent organic group of an aromatic tetracarboxylic acid that does not contain fluorine, but does not contain a carboxyl group; a tetravalent organic group of an aliphatic tetracarboxylic acid that does not contain a carboxyl group, for example, group A is any one of the following groups:
[0014] ;
[0015] B represents at least one of the following groups: a divalent organic group of an aromatic diamine that does not contain fluorine and does not contain an amino group; a divalent organic group of an aliphatic diamine whose relative molecular mass does not exceed 500 and does not contain an amino group; for example, B is any one of the following groups:
[0016] ;
[0017] L represents at least one of the following groups: containing polyethylene glycol diamine (NH2-(CH2O) n -CH2-CH2-NH2) divalent organic group, excluding amino groups, n is an integer greater than 1 and less than 10 (for example, n is 2, 3, 4, 5, 6, 7, 8, 9 or 10); for example, L is derived from any one of the following monomers:
[0018] ;
[0019] M is an imidazole organic compound, which reacts with the carboxyl group of polyamic acid to form a water-soluble polyamic acid salt, and its characteristics are as follows:
[0020] wherein X1 to X4 each represent a hydrogen atom or an alkane group having less than 5 carbon atoms;
[0021] ;
[0022] The preparation method of the polyamic acid imidazole salt as described above comprises the following steps:
[0023] (1) First, at room temperature, a diamine monomer containing B and L is dissolved in deionized water, and then at least one imidazole product in M is added to the solution and stirred for at least 1 hour to prepare a transparent solution, and then a dianhydride monomer containing an A group is added and dissolved in the aforementioned solution, wherein the molar ratio of the monomer containing an A group to the monomer containing a B group is 0.99-1.1:1, the solution concentration is controlled at 10-30wt%, and the molar number of C is 2.5 times or more of the molar number of A;
[0024] (2) Under an inert gas environment, react the mixture in the above (1) for at least 4 hours to obtain an aqueous polyimide precursor solution, wherein the aqueous polyimide precursor solution is a polyamic acid imidazole salt solution.
[0025] The use of the polyamic acid imidazole salt as described above or the polyamic acid imidazole salt prepared by the method as described above as an electrode binder in a lithium ion battery comprises the following steps:
[0026] 1) Steps for manufacturing electrodes: dissolving the negative electrode active material (the negative electrode active material is silicon, graphite or silicon-carbon composite material), conductive agent and polyimide precursor solution in deionized water, and mixing them evenly using magnetic stirring and ultrasonic waves; using a coating preparation device to evenly coat the slurry on one side of the current collector; the loading amount of the negative electrode active material and the mass fraction of the polyimide precursor solution are 0.2-2 mg·cm -2 and 2wt%-8wt%;
[0027] 2) drying the coated electrode in a forced air oven at 40°C-110°C for 0.1-10h, and then transferring it to a vacuum oven or treating it in a tube furnace protected by an inert gas at a higher temperature (120°C-350°C) for 0.1-12h to complete the imidization process of the polyimide precursor;
[0028] 3) The current collector after solvent drying is made into a circular electrode sheet with a diameter of 10-14 mm on a manual slicer; the mass of the electrode material on the electrode sheet can be calculated by weighing the mass before and after coating;
[0029] 4) Complete the installation of the lithium-ion battery buckle.
[0030] The use of the polyamic acid imidazole salt as described above or the polyamic acid imidazole salt prepared by the method as described above, wherein the polyamic acid imidazole salt solution is used to prepare a polyimide film, comprises the following steps:
[0031] The obtained aqueous polyimide precursor solution is directly cast on a glass plate or a stainless steel plate, cast into a film at room temperature, dried at 40-100°C for 0.1-24h to form a film, then vacuum dried at 80-120°C for 0.1-24h, and vacuum treated at 120°C-350°C for 0.1-12h to complete the imidization process and obtain a polyimide film.
[0032] Specifically, a polyamic acid imidazole salt containing a copolymer of polyethylene glycol-based diamine and dianhydride-based monomers, which is generated by reacting raw materials containing a dianhydride component and a diamine component, and contains the following repeating structural units:
[0033] ;
[0034] Wherein: x+y=1, 0≤x≤1, 0≤y≤1; for example, x is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1. For example, y is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1. A represents at least one of the following groups: a tetravalent organic group of an aromatic tetracarboxylic acid that does not contain fluorine, and does not contain a carboxyl group; a tetravalent organic group of an aliphatic tetracarboxylic acid that does not contain a carboxyl group; for example, A is derived from any one of the following monomers:
[0035] ;
[0036] B represents at least one of the following groups: a divalent organic group of an aromatic diamine without fluorine, whose solubility in water is greater than 0.1 g / L (25°C) and does not contain an amino group; a divalent organic group of an aliphatic diamine, whose relative molecular mass does not exceed 500 and does not contain an amino group; for example, B is derived from any one of the following monomers:
[0037] ;
[0038] L is a divalent organic group of polyethylene glycol diamine, does not contain an amino group, and has a general structural formula of:
[0039] ;
[0040] Wherein, n≥2, for example, n is 2, 4, 6, 8 or 10. For example, L is derived from any one of the following monomers:
[0041] ;
[0042] M is an imidazole organic compound, which reacts with the carboxyl group of polyamic acid to form a water-soluble polyamic acid salt, and its characteristics are as follows:
[0043] ;
[0044] Wherein, X1 to X4 represent a hydrogen atom or an alkane group having less than 5 carbon atoms.
[0045] The method for preparing an aqueous polyimide precursor solution containing a copolymer of polyethylene glycol-type diamine and dianhydride-type monomers of the present invention comprises the following steps:
[0046] (1) At room temperature, firstly dissolve the diamine monomer containing B and L in deionized water, then add at least one imidazole product in M to the solution, stir for at least 1 hour, and prepare a transparent solution, then add the dianhydride monomer containing A group, and also dissolve it in the above solution, the molar ratio of A to B monomer is 0.99-1.10:1, the solution concentration is controlled at 10-30wt%, and the molar ratio of L is 2.5 times or more of A;
[0047] (2) Under an inert gas environment, react the mixture in (1) for at least 6 hours to obtain an aqueous polyimide precursor solution having a certain viscosity.
[0048] The use of the aqueous polyimide precursor solution containing the copolymer of polyethylene glycol diamine and dianhydride monomers obtained by the above method as an electrode binder in a lithium ion battery comprises the following steps:
[0049] 1) Steps for manufacturing electrodes: dissolve the negative electrode active material (including but not limited to silicon, graphite or silicon-carbon composite materials, etc.), conductive agent, and polyimide precursor solution in deionized water, and mix them evenly using magnetic stirring and ultrasonic waves; use a coating preparation device to evenly coat the slurry on one side of the current collector; the loading amount of the negative electrode active material and the mass fraction of the polyimide precursor solution are 0.2-2 mg·cm -2 and 2wt%-8wt%;
[0050] 2) drying the coated electrode in a forced air oven at 40°C-110°C for 0.1-10h, and then transferring it to a vacuum oven or treating it in a tube furnace protected by an inert gas at a higher temperature (120°C-350°C) for 0.1-12h to complete the imidization process of the polyimide precursor;
[0051] 3) The current collector after solvent drying is made into a circular electrode sheet with a diameter of 10-14 mm on a manual slicer; the mass of the electrode material on the electrode sheet can be calculated by weighing the mass before and after coating;
[0052] 4) Complete the installation of the lithium-ion battery buckle.
[0053] The aqueous polyimide precursor solution containing the copolymer of polyethylene glycol diamine and dianhydride monomers obtained in the present invention is used as a method for preparing a polyimide film, comprising the following steps:
[0054] The obtained aqueous polyimide precursor solution containing a copolymer of polyethylene glycol and dianhydride monomers is directly cast on a glass plate or a stainless steel plate, cast into a film at room temperature, dried at 40-100°C for 0.1-24h to form a film, then vacuum dried at 80-120°C for 0.1-24h, and vacuum treated at 120°C-350°C for 0.1-12h to complete the imidization process, thereby obtaining a polyimide film.
[0055] The beneficial results of the present invention are:
[0056] (1) The present invention discloses a copolymer containing polyethylene glycol diamine and dianhydride monomers with mild polymerization conditions and harmless solvents. It can be used to prepare polyimide with excellent organic solvent resistance and containing flexible fatty chains and ether bonds on the main chain;
[0057] (2) The precursor solution containing the copolymer of polyethylene glycol diamine and dianhydride monomer in (2) above is applied to lithium-ion batteries and has good bonding properties and excellent battery performance;
[0058] (3) The polyimide membrane prepared from the copolymer of polyethylene glycol-containing diamine and dianhydride monomers has good thermal stability and mechanical properties. The polymer decomposition temperature can reach 300-500°C, the tensile strength can reach 80-120Mpa, and the elongation at break can reach 30-200%;
[0059] (4) The separator in (3) above is applied to lithium-ion batteries and has excellent cycle capacity and stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] Figure 1 The cycle performance curve of the silicon electrode prepared in Example 2 in a lithium-ion battery test device at room temperature;
[0061] Figure 2 This is the peeling force curve of the silicon electrode sheet prepared in Example 2. DETAILED DESCRIPTION
[0062] The technical solution of the present invention is described in detail below through specific embodiments, but it should be clearly stated that these embodiments are for illustration and are not to be construed as limiting the scope of the present invention.
[0063] Example 1
[0064] (1) In a 500 mL three-necked flask equipped with a nitrogen inlet and outlet, first dissolve p-phenylenediamine (PDA) (8.65 g, 0.08 mol) and 1,8-diamino-3,6-dioxaoctane (2PEG) (2.96 g, 0.02 mol) in deionized water, then add 1,2-dimethylimidazole (DMIZ) (24.03 g, 0.25 mol) and mechanically stir for 1 h at 25 ° C to prepare a transparent solution. Then add 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) (29.42 g, 0.1 mol) and dissolve it in the above solution, mechanically stir for 18 h at 70 ° C, and the solid content of the solution is controlled at 15 wt%; obtain a water-based polyimide precursor solution;
[0065] (2) The obtained aqueous polyimide precursor solution is directly cast on a glass plate or a stainless steel plate, cast into a film at room temperature, dried at 60°C for 5 hours, and then vacuum dried at 120°C for 1 hour. The imidization process is completed at 180°C for 6 hours to obtain a polyimide film with a film thickness of (50-60um);
[0066] (3) Table 1 summarizes the properties of aqueous polyimide precursor solutions and polyimides.
[0067] The application of the aqueous polyimide precursor solution of the present invention comprises the following steps:
[0068] The obtained aqueous polyimide precursor solution is used in a lithium ion battery device.
[0069] 1) Preparation of silicon negative electrode for lithium-ion battery. The general steps for preparing the negative electrode are as follows: Mix the aqueous polyimide precursor solution with deionized water, conductive carbon black (TIMCAL, Super C45), and nanosilicon (Canrd, 80-100nm) in a mass ratio of 10:10:80, and stir magnetically for 24 hours. After ultrasonic treatment for 30 minutes, the obtained slurry is coated on copper foil with a scraper (coating thickness is 100um). The prepared electrode is dried at 60°C for 1 hour, and then vacuum treated at 150°C for 6 hours to obtain a silicon negative electrode sheet. The silicon loading is controlled at 1.0-1.2 mg / cm 2 ;
[0070] 2) All battery assemblies were carried out in an argon atmosphere glove box, and the water and oxygen content in the glove box was less than 0.1ppm. The prepared electrode sheet was used as the working electrode, the metal lithium sheet was used as the negative electrode, and a mixture containing 1.0 mol / L lithium hexafluorophosphate (LiPF6) (based on the total volume of the electrolyte), ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, and 10% by volume (based on the total volume of the electrolyte) of fluoroethylene carbonate (FEC) additive was used as the electrolyte. Figure 1 After the packaged button cell is left to stand for 12 hours, the cycle performance test can be carried out: after 2 cycles of activation at 1.0A / g, the test starts at 4.2A / g and the temperature is 25°C.
[0071] Example 2:
[0072] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, firstly, PDA (6.49g, 0.06mol) and 2PEG (5.92g, 0.04mol) were dissolved in deionized water, and then DMIZ (24.03g, 0.25 mol) was added and mechanically stirred at 25°C for 1h to prepare a transparent solution. Then, BPDA monomer (29.42g, 0.1mol) was added and dissolved in the aforementioned solution, and mechanically stirred at 70°C for 18h. The solid content of the solution was controlled at 15wt%; an aqueous polyimide precursor solution was obtained. The remaining experimental steps and application steps were the same as those in Example 1.
[0073] Figure 1 The cycling performance curve of the binder prepared for Example 2 and applied to the silicon-based half-cell was tested at 25°C. After 2 cycles of charge and discharge at 1.0 A / g, the battery was charged and discharged for 100 cycles at a high current density of 4.2 A / g. Even at a high current density of 4.2 A / g, the battery still had excellent cycle capacity and stability: after 100 cycles of charge and discharge, the battery still had a high capacity of 2361 mAh / g and a capacity retention rate of 63.3%.
[0074] Figure 2 The 180° peeling curve of the electrode piece prepared for Example 2 is as follows: For a 20mm sample, fix the 3M tape on the steel plate, and fix the copper foil side of the sample on the 3M tape (Canrd, pole piece bonding force measurement tape); and use another 3M tape to stick the bonding layer of the sample. Use a universal tensile testing machine to perform a 180° peel test. The test results show that the adhesive prepared in Example 2 has excellent bonding performance, and the peel force is as high as 25N, proving that the introduction of polyethylene glycol segments can improve the peeling performance of the pole piece.
[0075] Example 3:
[0076] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, firstly, PDA (6.49g, 0.06mol) and 2PEG (5.92g, 0.04mol) were dissolved in deionized water, and then DMIZ (24.03g, 0.25 mol) was added and mechanically stirred at 25°C for 1h to prepare a transparent solution. Then, BPDA monomer (29.42g, 0.1mol) was added and dissolved in the aforementioned solution, and mechanically stirred at 70°C for 18h. The solid content of the solution was controlled at 15wt%; an aqueous polyimide precursor solution was obtained. The remaining experimental steps and application steps were the same as those in Example 1.
[0077] Example 4:
[0078] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, firstly, p-PDA (8.65g, 0.08mol) and 3,6,9-trioxaundecane-1,11-diamine (3PEG) (3.84g, 0.02mol) were dissolved in deionized water, and then DMIZ (24.03g, 0.25 mol) was added and mechanically stirred at 25°C for 1h to prepare a transparent solution. Then, BPDA monomer (29.42g, 0.1mol) was added and dissolved in the aforementioned solution, and mechanically stirred at 70°C for 18h. The solid content of the solution was controlled at 15wt% to obtain a water-based polyimide precursor solution. The remaining experimental steps and application steps were the same as those in Example 1.
[0079] Example 5:
[0080] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, firstly, PDA (6.49g, 0.06mol) and 3PEG (7.68g, 0.04mol) were dissolved in deionized water, and then DMIZ (24.03g, 0.25 mol) was added and mechanically stirred at 25℃ for 1h to prepare a transparent solution. Then, BPDA monomer (29.42g, 0.1mol) was added and dissolved in the aforementioned solution, and mechanically stirred at 70℃ for 18h. The solid content of the solution was controlled at 15wt%; an aqueous polyimide precursor solution was obtained. The remaining experimental steps and application steps were the same as those in Example 1.
[0081] Example 6:
[0082] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, firstly, p-PDA (8.65g, 0.08mol) and 2PEG (2.96g, 0.02mol) were dissolved in deionized water, and then DMIZ (24.03g, 0.25 mol) was added and mechanically stirred at 25°C for 1h to prepare a transparent solution. Then, 4,4'-oxydiphthalic anhydride (ODPA) (31.02g, 0.1mol) was added and dissolved in the aforementioned solution, and mechanically stirred at 70°C for 18h. The solid content of the solution was controlled at 15wt%; an aqueous polyimide precursor solution was obtained. The remaining experimental steps and application steps were the same as those in Example 1.
[0083] Example 7:
[0084] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, firstly, PDA (8.65g, 0.08mol) and 3PEG (3.84g, 0.02mol) were dissolved in deionized water, and then DMIZ (24.03g, 0.25 mol) was added and mechanically stirred at 25°C for 1h to prepare a transparent solution. Then, ODPA monomer (31.02g, 0.1mol) was added and dissolved in the aforementioned solution, and mechanically stirred at 70°C for 18h. The solid content of the solution was controlled at 15wt%; an aqueous polyimide precursor solution was obtained. The remaining experimental steps and application steps were the same as those in Example 1.
[0085] Example 8:
[0086] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, firstly, p-PDA (8.65g, 0.08mol) and 2PEG (2.96g, 0.02mol) were dissolved in deionized water, and then DMIZ (24.03g, 0.25 mol) was added and mechanically stirred at 25°C for 1h to prepare a transparent solution. Then, 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) monomer (32.22g, 0.1mol) was added and dissolved in the aforementioned solution, and mechanically stirred at 70°C for 18h. The solid content of the solution was controlled at 15wt% to obtain a water-based polyimide precursor solution. The remaining experimental steps and application steps were the same as those in Example 1.
[0087] Example 9:
[0088] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, firstly, PDA (8.65g, 0.08mol) and 3PEG (4.41g, 0.02mol) were dissolved in deionized water, and then DMIZ (24.03g, 0.25 mol) was added and mechanically stirred at 25℃ for 1h to prepare a transparent solution. Then, BTDA monomer (32.22g, 0.1mol) was added and dissolved in the aforementioned solution, and mechanically stirred at 70℃ for 18h. The solid content of the solution was controlled at 15wt%; an aqueous polyimide precursor solution was obtained. The remaining experimental steps and application steps were the same as those in Example 1.
[0089] Example 10:
[0090] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, firstly, p-PDA (8.65g, 0.08mol) and 2PEG (2.96g, 0.02mol) were dissolved in deionized water, and then DMIZ (24.03g, 0.25 mol) was added and mechanically stirred at 25°C for 1h to prepare a transparent solution. Then, 3,3,4,4-diphenylsulfone tetracarboxylic dianhydride (DSDA) monomer (35.83g, 0.1mol) was added and dissolved in the aforementioned solution, and mechanically stirred at 70°C for 18h. The solid content of the solution was controlled at 15wt%; an aqueous polyimide precursor solution was obtained. The remaining experimental steps and application steps were the same as those in Example 1.
[0091] Example 11:
[0092] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, firstly, PDA (8.65g, 0.08mol) and 3PEG (4.41g, 0.02mol) were dissolved in deionized water, and then DMIZ (24.03g, 0.25 mol) was added and mechanically stirred at 25℃ for 1h to prepare a transparent solution. Then, DSDA monomer (35.83g, 0.1mol) was added and dissolved in the aforementioned solution, and mechanically stirred at 70℃ for 18h. The solid content of the solution was controlled at 15wt%; an aqueous polyimide precursor solution was obtained. The remaining experimental steps and application steps were the same as those in Example 1.
[0093] Example 12:
[0094] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, firstly, p-PDA (8.65g, 0.08mol) and 2PEG (2.96g, 0.02mol) were dissolved in deionized water, and then DMIZ (24.03g, 0.25 mol) was added and mechanically stirred at 25°C for 1h to prepare a transparent solution. Then, cyclobutanetetracarboxylic dianhydride (CBDA) (19.61g, 0.1mol) was added and dissolved in the aforementioned solution, and mechanically stirred at 70°C for 18h. The solid content of the solution was controlled at 15wt% to obtain a water-based polyimide precursor solution. The remaining experimental steps and application steps were the same as those in Example 1.
[0095] Example 13:
[0096] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, firstly, PDA (8.65g, 0.08mol) and 3PEG (4.41g, 0.02mol) were dissolved in deionized water, and then 1.25 times the carboxylic acid equivalent of DMIZ (24.03g, 0.25 mol) was added and mechanically stirred at 25°C for 1h to prepare a transparent solution. Then, CBDA monomer (19.61g, 0.1mol) was added and dissolved in the aforementioned solution, and mechanically stirred at 70°C for 18h. The solid content of the solution was controlled at 15wt%; an aqueous polyimide precursor solution was obtained. The remaining experimental steps and application steps were the same as those in Example 1.
[0097] Example 14:
[0098] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, firstly, p-PDA (8.65g, 0.08mol) and 2PEG (2.96g, 0.02mol) were dissolved in deionized water, and then DMIZ (24.03g, 0.25 mol) was added and mechanically stirred at 25°C for at least 1h to prepare a transparent solution. Then, 2,3,3',4'-biphenyltetracarboxylic acid dianhydride (α-BPDA) monomer (29.42g, 0.1mol) was added and dissolved in the aforementioned solution, and mechanically stirred at 70°C for 18h. The solid content of the solution was controlled at 15wt%; an aqueous polyimide precursor solution was obtained. The remaining experimental steps and application steps were the same as those in Example 1.
[0099] Example 15:
[0100] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, firstly, p-PDA (8.65g, 0.08mol) and 3PEG (4.41g, 0.02mol) were dissolved in deionized water, and then DMIZ (24.03g, 0.25 mol) was added and mechanically stirred at 25℃ for 1h to prepare a transparent solution. Then, α-BPDA monomer (29.42g, 0.1mol) was added and dissolved in the aforementioned solution and mechanically stirred at 70℃ for 18h. The solid content of the solution was controlled at 15wt% to obtain a water-based polyimide precursor solution. The remaining experimental steps and application steps were the same as those in Example 1.
[0101] Comparative Example 1:
[0102] In this example, a polyimide precursor solution without polyethylene glycol diamine during copolymerization is used as a comparative example: in an inert gas environment, firstly, PDA (10.81 g, 0.10 mol) is dissolved in deionized water, and then DMIZ (24.03 g, 0.25 mol) is added, and mechanically stirred for 1 h at 25°C to prepare a transparent solution. Then, BPDA (29.42 g) monomer is added and dissolved in the aforementioned solution, and mechanically stirred for 18 h at 70°C, and the solid content of the solution is controlled at 15 wt%; an aqueous polyimide precursor solution is obtained. The remaining experimental steps and application steps are the same as those in Example 1.
[0103] Comparative Example 2:
[0104] This example uses polyacrylic acid (Aladdin, weight average molecular weight is 450,000) as a comparative example, and its application steps are the same as Example 1.
[0105] Comparative Example 3:
[0106] This example uses commercially available sodium carboxymethyl cellulose (DAICEL, CMC-2200) as a comparative example, and its application steps are the same as those of Example 1.
[0107] Table 1 Test method for data
[0108] Intrinsic viscosity dL g-1 test method: prepare the test sample into a 5 mg / L solution, use an Ubbelohde viscometer to measure the solvent retention time t0 / s and the test sample retention time t / s, and calculate the intrinsic viscosity according to the following formula:
[0109] ;
[0110] Rotational viscosity Pa s test method: test with a rheometer at 50°C;
[0111] Test method for glass transition temperature ℃: Prepare polyacrylic acid / polyimide composite film into 40mm The 8mm sample was loaded on a dynamic thermomechanical analyzer, and the measurement temperature range was 50-350°C, with a heating rate of 5°C / min. The glass transition temperature was obtained based on the changes in the storage modulus and loss modulus.
[0112] Elastic modulus Gpa Elastic strength Mpa Elongation at break % Test method: Prepare polyacrylic acid / polyimide composite film into 60mm The sample was 10 mm thick and loaded on a universal tensile testing machine with a tensile rate of 50 mm / min.
[0113] Table 1
[0114]
[0115] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A polyamic acid imidazole salt containing a copolymer of polyethylene glycol-based diamine and dianhydride-based monomers, which is produced by reacting raw materials including a dianhydride component and a diamine component, characterized in that: A copolymer comprising the following repeating structural units: ; Among them, x+y=1, 0≤x≤1, 0≤y≤1; A represents at least one of the following groups: a tetravalent organic group of an aromatic tetracarboxylic acid that does not contain fluorine, but does not contain a carboxyl group; a tetravalent organic group of an aliphatic tetracarboxylic acid that does not contain a carboxyl group, for example, group A is any one of the following groups: ; B represents at least one of the following groups: a divalent organic group of an aromatic diamine that does not contain fluorine and does not contain an amino group; a divalent organic group of an aliphatic diamine whose relative molecular mass does not exceed 500 and does not contain an amino group; for example, B is any one of the following groups: ; L represents at least one of the following groups: containing polyethylene glycol diamine (NH2-(CH2O) n -CH2-CH2-NH2) divalent organic group, excluding amino groups, n is an integer greater than 1 and less than 10; for example, L is derived from any one of the following monomers: ; M is an imidazole organic compound, which reacts with the carboxyl group of polyamic acid to form a water-soluble polyamic acid salt, and its characteristics are as follows: wherein X1 to X4 each represent a hydrogen atom or an alkane group having less than 5 carbon atoms; 。 2. The method for preparing the polyamic acid imidazole salt according to claim 1, characterized in that: The steps include: (1) First, at room temperature, a diamine monomer containing B and L is dissolved in deionized water, and then at least one imidazole product in M is added to the solution and stirred for at least 1 hour to prepare a transparent solution, and then a dianhydride monomer containing an A group is added and dissolved in the aforementioned solution, wherein the molar ratio of the monomer containing an A group to the monomer containing a B group is 0.99-1.1:1, the solution concentration is controlled at 10-30wt%, and the molar number of C is 2.5 times or more of the molar number of A; (2) Under an inert gas environment, react the mixture in the above (1) for at least 4 hours to obtain an aqueous polyimide precursor solution, wherein the aqueous polyimide precursor solution is a polyamic acid imidazole salt solution.
3. The use of the polyamic acid imidazole salt prepared by the method according to claim 2, characterized in that: As an electrode binder, it is used in lithium-ion batteries, comprising the following steps: 1) Steps for manufacturing electrodes: dissolving the negative electrode active material (the negative electrode active material is silicon, graphite or silicon-carbon composite material), conductive agent and polyimide precursor solution in deionized water, and mixing them evenly using magnetic stirring and ultrasonic waves; using a coating preparation device to evenly coat the slurry on one side of the current collector; the loading amount of the negative electrode active material and the mass fraction of the polyimide precursor solution are 0.2-2 mg·cm -2 and 2wt%-8wt%; 2) drying the coated electrode in a forced air oven at 40°C-110°C for 0.1-10h, and then transferring it to a vacuum oven or treating it in a tube furnace protected by an inert gas at a higher temperature (120°C-350°C) for 0.1-12h to complete the imidization process of the polyimide precursor; 3) The current collector after solvent drying is made into a circular electrode sheet with a diameter of 10-14 mm on a manual slicer; the mass of the electrode material on the electrode sheet can be calculated by weighing the mass before and after coating; 4) Complete the installation of the lithium-ion battery buckle.
4. The use of the polyamic acid imidazole salt prepared by the method according to claim 2, characterized in that: The polyamic acid imidazole salt solution is used to prepare a polyimide film, comprising the following steps: The obtained aqueous polyimide precursor solution is directly cast on a glass plate or a stainless steel plate, cast into a film at room temperature, dried at 40-100°C for 0.1-24h to form a film, then vacuum dried at 80-120°C for 0.1-24h, and vacuum treated at 120°C-350°C for 0.1-12h to complete the imidization process and obtain a polyimide film.